2007
DOI: 10.3141/2037-02
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Analytical Investigations of Mechanistic Effects of Dowel Misalignment in Jointed Concrete Pavements

Abstract: This paper presents the results of experimental and analytical investigations on the effects of dowel misalignment on the joint opening behavior and distress in concrete pavement joints. It focuses on the development of three-dimensional (3-D) finite element models for computing the complex stress states and resulting damage in concrete pavement joints with misaligned dowels and, through experimental results, their validation. The concrete pavement is modeled by using a damage–plasticity material model, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
0
10
0
3
Order By: Relevance
“…Also, this selection was made to keep the distress surrounding the dowel bar localized without significant cracking during opening of the joint by 12 mm [10] to allow for the evaluation of LTE under cyclic load, after the slabs were pulled out and pushed back representing slab movement. Previous studies [5,10,11] showed that 12.5 mm misalignment (per half-length of the dowel) did not cause global failure of specimen. The third value of misalignment magnitude (25 mm) was adopted to investigate the effect of high misalignment magnitude as well as failure mechanism of the specimens due to joint lockup.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…Also, this selection was made to keep the distress surrounding the dowel bar localized without significant cracking during opening of the joint by 12 mm [10] to allow for the evaluation of LTE under cyclic load, after the slabs were pulled out and pushed back representing slab movement. Previous studies [5,10,11] showed that 12.5 mm misalignment (per half-length of the dowel) did not cause global failure of specimen. The third value of misalignment magnitude (25 mm) was adopted to investigate the effect of high misalignment magnitude as well as failure mechanism of the specimens due to joint lockup.…”
Section: Methodsmentioning
confidence: 87%
“…The results showed no signifcant difference in pull-out load for single misaligned dowel specimens, whereas a significant increase in pull-out load was observed for the specimens containing two misaligned dowels when the misalignment magnitude exceeded 12.7 mm per half dowel length.It should be noted that there are multiple dowels bars along a typical transverse joint and the interaction effect during pull-out can not be ignored [9]. Prabhu et al [5,10,11] carried out experimental as well as numerical investigations to produce guidelines for allowable dowel misalignment. Their investigations involved one, two, three and five 32 mm diameter steel dowel bars with different misalignment magnitudes (0, 6.35, 12.7, 19, and 25.4 mm per half-length of the dowel bar) and different misalignment types (vertical, horizontal and combined).…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decades, investigations on concrete pavements mechanical behavior employing the finite element method (FEM) have increasingly spread. Most of these studies are concentrated on the load transfer efficiency analysis in concrete pavement joints with aligned dowel bars [13]. Only a limited number of investigations sought to understand the interaction mechanism between misaligned dowel bars and the concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Only a limited number of investigations sought to understand the interaction mechanism between misaligned dowel bars and the concrete. Examples of such studies can be found elsewhere [13], [14], [15], [16].…”
Section: Introductionmentioning
confidence: 99%